2012
DOI: 10.1159/000338800
|View full text |Cite
|
Sign up to set email alerts
|

Serial Monitoring of Soluble Interleukin Family Member ST2 in Patients with Acutely Decompensated Heart Failure

Abstract: Objectives: To determine whether serial measures of the interleukin receptor family member soluble ST2 (sST2) provide additional prognostic information to baseline measures for long-term risk stratification of acutely decompensated heart failure (ADHF) patients. Methods: We prospectively enrolled 72 ADHF patients. Blood samples were collected to measure sST2 concentrations at presentation and on day 4 of hospitalization. All patients were clinically followed, and vital status was registered. Results: Between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
47
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 68 publications
8
47
0
4
Order By: Relevance
“…107 Similar to chronic HF, serial measurement adds value to a baseline concentration of sST2. Several cohorts have now shown that posttreatment concentrations of sST2 more powerfully predict death compared with baseline values [182][183][184] and in general provide superior prognostic information to other markers, including BNP or NT-proBNP, in this regard. 155 In addition to the natriuretic peptides, there is a substantial literature on other biomarkers at the time of AHF hospitalization and subsequent risk.…”
Section: P<0001)mentioning
confidence: 99%
“…107 Similar to chronic HF, serial measurement adds value to a baseline concentration of sST2. Several cohorts have now shown that posttreatment concentrations of sST2 more powerfully predict death compared with baseline values [182][183][184] and in general provide superior prognostic information to other markers, including BNP or NT-proBNP, in this regard. 155 In addition to the natriuretic peptides, there is a substantial literature on other biomarkers at the time of AHF hospitalization and subsequent risk.…”
Section: P<0001)mentioning
confidence: 99%
“…Similarly, the highsST2 group benefited most from beta-blocker therapy in other settings. 37,38) sST2 might be used to help clinicians with decision-making and it is also a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…Although the sST2 levels in this study were similar to other reports of chronic HF, 7-9 levels of sST2 in patients with acute HF and post-MI are significantly higher but fall rapidly over days to weeks. 5,6,18,19 This may be part of an acute neurohormonal and inflammatory stress response that may not be present in clinically stable HF such as those enrolled in Val-HeFT.…”
Section: Discussionmentioning
confidence: 99%